2010
DOI: 10.1002/iroh.201011249
|View full text |Cite
|
Sign up to set email alerts
|

Enclosure Study on Phytoplankton Response to Stocking of Silver Carp (Hypophthalmichthys molitrix) in a Eutrophic Tropical Reservoir in South China

Abstract: A 10-week enclosure experiment was conducted in the dry season (October to December) to assess the impact of fish stocking on water quality and phytoplankton community at three stocking levels of silver carp (Hypophthalmichthys molitrix) (0, 16 and 50 g m -3 ) in a shallow, eutrophic tropical reservoir (Guangdong, South China). The nanophytoplankton (< 20 μm) accounted for 60 ± 5% of total biomass and Scenedesmus quadricauda was the predominant species (size: 16.5 ± 5 μm, relative biomass 27 ± 10%). Phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However, they require a large area, have low hydraulic load and exhibit intolerance to heavy pollutant loading rate [9], including the observation of seasonal death and plant diseases [68]. Therefore, living plants are recommended to be replaced by aqua mats and artificial seaweed, which can enhance the growth of microorganisms and overcome the above drawbacks [69]. Given the low removal rate of single constructed wetland, Bai et al [9] sequentially constructed floating bed wetland, horizontal subsurface flow constructed wetland and surface flow constructed wetland for the treatment of urban river water.…”
Section: Constructed Wetlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they require a large area, have low hydraulic load and exhibit intolerance to heavy pollutant loading rate [9], including the observation of seasonal death and plant diseases [68]. Therefore, living plants are recommended to be replaced by aqua mats and artificial seaweed, which can enhance the growth of microorganisms and overcome the above drawbacks [69]. Given the low removal rate of single constructed wetland, Bai et al [9] sequentially constructed floating bed wetland, horizontal subsurface flow constructed wetland and surface flow constructed wetland for the treatment of urban river water.…”
Section: Constructed Wetlandsmentioning
confidence: 99%
“…For example, the freshwater gastropod was used as a bioindicator to estimate the contamination levels of some heavy metals in river water and sediments [101]. Some aquatic animals, such as clams, snails, silver carp, common carp and other filter-feeding fish, are able to reduce concentrations of nutrients, eutrophication and algae in river water, and thus improve the water quality [69]. However, some studies reported that the capability of silver carp fish to control algal biomass is restricted by the toxic effects of the bio-toxins secreted by algae and by the presence of inorganic or organic contaminants in polluted water, which ultimately hamper the performance of this biological treatment system [83].…”
Section: Remediation By Aquatic Animalsmentioning
confidence: 99%
“…Unfortunately, high biomasses of silver carp have been generally used in biomanipulation research and few studies have involved low fish biomass (see review by Zhang et al, 2008). below 8 g m )3 ) on the plankton community containing large herbivorous cladocerans, although several studies involving the use of silver carp to control phytoplankton have been conducted (Starling, 1993;Datta & Jana, 1998;Starling et al, 1998;Xiao et al, 2010). For tropical fresh waters, no attempt, to our knowledge, has been made to assess the impact of low biomass of silver carp (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For tropical fresh waters, no attempt, to our knowledge, has been made to assess the impact of low biomass of silver carp (e.g. below 8 g m )3 ) on the plankton community containing large herbivorous cladocerans, although several studies involving the use of silver carp to control phytoplankton have been conducted (Starling, 1993;Datta & Jana, 1998;Starling et al, 1998;Xiao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high mass-specific nutrient excretion rate (Vanni, 2002), zooplankton is regarded as an important part of nutrient cycling in the water column. However, zooplanktons are frequently suppressed after the introduction of silver carp (Zhang et al, 2008;Xiao et al, 2010) in mesocosms such as the enclosures in the present study. The absence of large planktivorous zooplankton may reinforce the importance of fish in nutrient cycling.…”
Section: Discussionmentioning
confidence: 59%